THE PHENOMENON OF LANGUAGE GAMES AS COLLEGE STUDENTS RESPONSES TO THE REVISED CRIMINAL CODE DRAFT 2019: A SOCIOLINGUISTICS STUDY - Nurul Nisfu Syahriy; Ridwan Hanafiah; Rudy Sofyan (JOALL (Journal of Applied Linguistics and Literature), 2020)
A language game is a form of utterance that obtains various deviations, which is intended for various purposes and contains of more than one meaning that depends on how it used and to whom it is intended. In connection with this topic, this paper was made to analyze the phenomenon of language game originating from among students in some demonstrations aimed at the government especially the House of Parliament (DPR) regarding the revised criminal code draft (RUUKUHP) 2019 that was launched to be ratified. For this reason, the data used are portraits of posters and banners sourced from various cities in Indonesia with various forms of utterance. Accordingly, this study will analyze the data based on sociolinguistic studies to understand language problems related to the elements and functions of language. Data were analyzed using a descriptive qualitative method. Eventually, there were various forms of language games that were found such as, sound substitution, sound addition, abbreviations, metaphor, polysemic, idiom, entailment and rhyme. The language game mentioned was created with various objectives such as criticizing related policies, making fun of the related performance and just creating humor.